Prevention of ACL injury, Part II: Effects of ACL injury prevention programs on neuromuscular risk factors and injury rate - Dai, B.; Herman, D.; Liu, H.; Garrett, W. E.; Yu, B. (Research in Sports Medicine, 2012)
Prevention strategies have been developed based on existing knowledge in an attempt to alter neuromuscular control and lower extremity biomechanics in order to reduce anterior cruciate ligament (ACL) injury rates. These strategies have included different training programs ranging from injury education to multicomponent training. Many training programs have been demonstrated as resulting in altered lower extremity movement patterns. The effects of current training programs on ACL injury rate, however, are inconsistent. This review was focused on the effects of current ACL injury training programs on neuromuscular risk factors and ACL injury rate. Recommendations were made based on the available evidence for clinicians and coaches to implement ACL injury prevention programs.